Ekstrak Hirarki Data Dari Situs Web A-Z Animals Menggunakan Web Scraping - Darmawan, I Putu Arditya; Piarsa, I Nyoman; Arya Dharmaadi, I Putu (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017, 2017)
A-Z Animals is a website that presents data about Kingdom Animalia. The Kingdom Animalia d ata has a hierarchy or level called the taxon level, which starts from kingdom to species. The problems encountered are the data contained on the website can be reuse for other purposes, such as creating dictionaries, learning media and others, but it takes a long time to enter data into the database due to the many and the complexity of the data. The solution of the problem is to create an application that can automatically retrieve data from the website to speed up data collection.Web Scraping is a method to retrieve documents from a website from the internet, in the form of HTML, next analyzed to retrieve certain data from the document. The results of tests s owed applications can retrieve content or data required from the website a-z-animal.com. The application takes an average time to process one page of a-z-animal.com is about 16.13 seconds.